FAILURE ANALYSIS OF FRACTURED DENTAL IMPLANTS - Bansal R.; Sharma A.R.; Singh V. (My University, 2025)
The success and predictability of titanium implants over long periods of time are well established, and there has been a tremendous increase in implant popularity among patients and clinicians over the last four decades. However, complications can occur, resulting in the loss of both the implant and the prosthesis. Dental implant fracture is uncommon; however, implants or abutment screws can fracture and cause significant problems for both the clinician and the patient. Improper design, overload, fatigue, and corrosion are all potential causes of implant fracture. Six retrieved fractured dental implants of varying diameter and thread design were collected on a regular basis to characterize their fracture behavior by SEM and assess the fracture mechanism. The majority of the implants were fractured as a result of fatigue crack initiation and propagation from the thread roots. © 2022, Association of Metallurgical Engineers of Serbia. All rights reserved.